Maternal outcomes before and after new oxytocin protocol at cesarean delivery. Issue 2 (6th November 2021) - Kotze, Adri; Adam, Yasmin; Naidoo, Poovangela
Abstract: Objective: The primary objective was to describe the incidence of post‐partum hemorrhage at cesarean delivery before and after implementation of a new high dose oxytocin protocol at Chris Hani Baragwanath Academic Hospital. Methods: This was a cross sectional retrospective record review 3 months before and 3 months after the implementation of a high dose oxytocin protocol. The study included all women that underwent cesarean delivery between 1 November 2016 and 30 April 2017 with a gestation of >24 weeks. Results: A total of 4604 Cesarean deliveries were performed during the study period, 2162 before the implementation of the new protocol and 2442 after. The incidence of post‐partum hemorrhage was 4.8% ( n  = 91) in the Before group and 3.9% ( n  = 89) in the After group ( P  = 0.17). There was a 17.9% change in incidence of postpartum hemorrhage between the groups ( P  = 0.17). There was no significant difference in uterine atony between the Before and After groups (21.8% and 30.1%, P  = 0.30). Conclusion: There was no difference in the incidence of postpartum hemorrhage at cesarean delivery after the implementation of a high dose oxytocin protocol. Abstract : This is a clinical article describing the incidence of post‐partum hemorrhage before and after implementation of a new high dose oxytocin protocol. No difference in the incidence of postpartum hemorrhage at cesarean section was found after the implementation of this protocol.